A Population Pharmacokinetic Model to Inform Extension of the Eteplirsen Dosing Regimen Across the Broad DMD Population - Yogesh Patel; Larry Orogun; Nicole Yocum; Louise R. Rodino‐Klapac; Lilly East (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Duchenne muscular dystrophy (DMD) is characterized by progressive, irreversible muscle damage that usually leads to premature death from cardiac or respiratory failure. Eteplirsen is a phosphorodiamidate morpholino oligomer and the first antisense oligonucleotide (ASO) approved for the treatment of patients with exon 51 skip‐amenable DMD. This analysis presents the first population pharmacokinetics (PK) modeling and simulation performed for the ASO drug class in DMD. Study objectives were to characterize the population PK of eteplirsen in patients with DMD across a broad age range and to identify the impact of covariates on eteplirsen exposure to guide clinical dosing. Plasma concentration data were pooled from six clinical studies of male patients with DMD across the age range of 6 months to 4 years (1 study) and 4–16 years (5 studies). Doses ranged from 0.5 to 50 mg/kg/week across different studies. A three‐compartment model with a linear elimination described the eteplirsen plasma concentration data well. Body weight effect on all PK parameters and eGFR, and age (≤ 4 years vs. > 4 years) effect on systemic clearance were key determinants of variability in the final model. Simulations showed similar exposures for eteplirsen (30 mg/kg intravenously once weekly) across different age groups (0.5 to < 2, 2 to < 4, 4 to < 7, and 7 to ≤ 16 years). These findings support the existing eteplirsen dosing paradigm of uniform weight‐based dosing at 30 mg/kg/week across the broad age range of the target DMD population (6 months to adolescence).